A Liberalism of Sincerity: The Role of Religion in the Public Square - Helfand, Michael A. (Journal of law, religion and state, 2012)
This article considers the extent to which the liberal nation-state ought to accommodate religious practices that contravene state law and to incorporate religious discourse into public debate. To address these questions, the article develops a liberalism of sincerity based on John Locke’s theory of toleration. On such an account, liberalism imposes a duty of sincerity to prevent individuals from consenting to a regime that exercises control over matters of core concern such as faith, religion, and conscience. Liberal theory grounds the legitimacy of the state in the consent of the governed, but consenting to an intolerant regime is illegitimate because it empowers government to demand insincere conduct. Thus, demanding that citizens pursue sincerity ensures that they do not consent away their individual liberties in exchange for promises of security and orderliness.